(untitled) (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2023)
Several cities/districts in the province of Bali have not reached the target for providing exclusive breastfeeding, namely Jembrana Regency (47.6%), and Denpasar City (47.6%). One solution to increase exclusive breastfeeding is through counseling or an approach or the term coparenting, namely cooperation between the mother and other families by providing support to the mother. The aim of the research is to provide education to mothers regarding the Asah Asih and Asuh coparenting mode which can increase exclusive breastfeeding. This research used cross sectional research and was conducted in September – November 2023 at PMB Bdn. Luh Ayu Koriawati., S.Tr.Keb with a sample size of 30 respondents. Data analysis used an independent sample T-Test to show differences in knowledge regarding Exclusive Breastfeeding and the Coparenting Model before and after being given counseling. The test results show that there is an increase in the pre-test knowledge score, namely 73.33 compared to the post-test, namely 80.67. with P value = 0.022 (smaller than 0.05). Based on the research results, it is hoped that the Balinese culture-based coparenting model can become a program to increase exclusive breastfeeding behavior with family (husband) assistance.